2002
DOI: 10.1161/hq0202.103997
|View full text |Cite
|
Sign up to set email alerts
|

Amount of H Antigen Expressed on Circulating von Willebrand Factor Is Modified by ABO Blood Group Genotype and Is a Major Determinant of Plasma von Willebrand Factor Antigen Levels

Abstract: To investigate whether the effect of ABO blood group on plasma von Willebrand factor (vWF) levels is mediated by the ABH antigenic determinants carried on N-linked glycans of vWF, we studied 158 group A and group O healthy volunteers. vWF antigen (vWF:Ag) and factor VIII antigen (FVIII:Ag) levels were highest in A(1)A(1) individuals and higher in A(1)O(1) than in A(2)O(1) or O(1)O(1) individuals. Plasma A transferase activity and the amount of A antigen expressed per unit vWF (AvWF) were significantly higher i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
147
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 128 publications
(158 citation statements)
references
References 35 publications
11
147
0
Order By: Relevance
“…These results favor the hypothesis that the expression of H antigen on VWF is one of the most important determinants of circulating levels of VWF:Ag. 8 In conclusion, we demonstrated that the circulating levels of VWF:Ag and FVIII in subjects with rare subgroups were similar to those found in group O individuals. These data could contribute to the diagnosis of von Willebrand's disease and to the evaluation of thrombophilia in individuals with different ABO subgroups.…”
Section: Resultssupporting
confidence: 73%
“…These results favor the hypothesis that the expression of H antigen on VWF is one of the most important determinants of circulating levels of VWF:Ag. 8 In conclusion, we demonstrated that the circulating levels of VWF:Ag and FVIII in subjects with rare subgroups were similar to those found in group O individuals. These data could contribute to the diagnosis of von Willebrand's disease and to the evaluation of thrombophilia in individuals with different ABO subgroups.…”
Section: Resultssupporting
confidence: 73%
“…The A and B alleles of the ABO locus encode A and B glycosyltransferase activities, which convert precursor H antigen into either A or B determinants, the A and B antigens having an extra saccharide unit to the O unit (N-acetylgalactosamine and galactose, respectively). Group O individuals lack such transferase enzymes (loss of function) and express basic, unchanged H-antigen (7,8).…”
Section: Introductionmentioning
confidence: 99%
“…VWF concentration in each fraction was determined using a specific VWF enzyme-linked immunosorbent assay (ELISA), as previously described. 22 The purity of VWF was assessed by reducing SDS-PAGE and silver staining. …”
mentioning
confidence: 99%